Transcriptome analysis reveals the roles of nitrogen metabolism and sedoheptulose bisphosphatase pathway in methanol‐dependent growth of Corynebacterium glutamicum - Fan, Liwen; Wang, Yu; Qian, Jin; Gao, Ning; Zhang, Zhihui; Ni, Xiaomeng; Sun, Letian; Yuan, Qianqian; Zheng, Ping; Sun, Jibin (Microbial biotechnology, 2021)
Summary Methanol is a promising feedstock for biomanufacturing of fuels and chemicals. Although efforts have been made to engineer platform microorganisms for methanol bioconversion, the substrate uptake and cell growth rates on methanol are still unsatisfactory, suggesting certain limiting factors remain unsolved. Herein, we analysed the global metabolic regulation changes between an evolved methanol‐dependent Corynebacterium glutamicum mutant and its ancestral strain by transcriptome analysis. Many genes involved in central metabolism including glycolysis, amino acid biosynthesis and energy generation were regulated, implying the adaptive laboratory evolution reprogrammed the cellular metabolism for methanol utilization. We then demonstrated that nitrate could serve as a complementary electron acceptor for aerobic methanol metabolism, and the biosynthesis of several amino acids limited methylotrophic growth. Finally, the sedoheptulose bisphosphatase pathway for generating methanol assimilation acceptor was found effective in C. glutamicum. This study identifies limiting factors of methanol metabolism and provides engineering targets for developing superior synthetic methylotrophs. Transcriptome analysis of methanol‐dependent Corynebacterium glutamicum reveals metabolic regulation changes in central metabolism. It is experimentally verified that nitrate could serve as an additional electron acceptor for aerobic methanol metabolism and the biosynthesis of several amino acids limits methylotrophic growth, and the SBPase variant for Ru5P regeneration is effective in methylotrophic C. glutamicum.